2014
DOI: 10.1016/j.bbr.2014.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in diazepam effects and parvalbumin-positive GABA neurons in trait anxiety Long Evans rats

Abstract: In clinical populations, prevalence rates for a number of anxiety disorders differ between males and females and gonadal hormones are thought to contribute to these differences. While these hormones have been shown to modulate the anxiolytic effects of the benzodiazepine agonist diazepam in some models, findings are inconsistent. Here, we tested for sex differences in response to anxiogenic stimuli following a 30-min diazepam (1.0 mg/kg) pre-treatment in male and female rats showing high (HAn) and low (LAn) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…The present results demonstrate that the densities of PVþ neurons are also sexually dimorphic in the amygdala of the guinea pig as they are also in several other brain regions of the rat (Stefanova et al, 1997b;Ravenelle et al, 2014). The pattern of sexual dimorphism in the case of PVþ neurons was in the amygdala quite similar to that found for CBþ cells.…”
Section: Discussionsupporting
confidence: 65%
“…The present results demonstrate that the densities of PVþ neurons are also sexually dimorphic in the amygdala of the guinea pig as they are also in several other brain regions of the rat (Stefanova et al, 1997b;Ravenelle et al, 2014). The pattern of sexual dimorphism in the case of PVþ neurons was in the amygdala quite similar to that found for CBþ cells.…”
Section: Discussionsupporting
confidence: 65%
“…This study was designed to extend our previous findings showing greater diazepam effects on EPM in males displaying high anxiety‐like behavior compared to females, and GABA neuron density positively correlating with low anxiety‐like behavior. While we did not show similar diazepam effects on females in that work, we did not isolate the stage of estrous (Ravenelle et al ., ). It is probable that given the variable stages of estrous for the females, there is greater variability in the female group.…”
Section: Introductionmentioning
confidence: 97%
“…Anti-anxiety drugs work, at least in part, by acting on PV-expressing GABA interneurons in the basolateral amygdala (Hale et al, 2010). Increases in PV-positive neurons have been demonstrated in the basolateral amygdala of rats reared in an enriched environment, and these changes are associated with reduced anxietylike behavior (Urakawa et al, 2013;Ravenelle et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that few PV + interneurons are shown in the CeA by immunoreactive methods in rats (Zahm et al, 2003; Ravenelle et al, 2014). The immunohistochemical images of Zahm et al (2003) show a small quantity cell body of PV + interneurons in the CeA, which is consistent with our immunofluorescence results using PV antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Although PV + interneurons are not the biggest interneuron population in the CeA, their function in the CeA has been indicated to be significantly related to anxiety-like behavior (Ravenelle et al, 2014). However, whether the plasticity of PV + interneurons of CeA can be modulated during drug withdrawal, and their function and neurophysiological mechanism in regulating negative affective symptoms during withdrawal, are largely unknown.…”
Section: Introductionmentioning
confidence: 99%